Laporan Studi Kelayakan Bisnis Pada DMNT Sportwear - Agus Sutardi; Cindy Oktavia Septiani; Ena Srilusyana; Intan Dinilah; Tarisa Rahmawati; Tika Kartika Rahman (Institut Nalanda, 2024)
A business feasibility study is a planned activity carried out to study in more depth about a business to be run, the effort will ultimately provide a conclusion about whether or not a business is feasible to run. DMNT Sportwear is the object of research, based on sports fashion production activities that are widely scattered in the market, making the author interested in researching and testing the feasibility of this business. The purpose of this research is to find out whether the DMNT Sportwear business is feasible to continue or not. The research method used is descriptive qualitative. In this study it was found that DMNT Sportwear's daily sales reached 1,500 pcs with a monthly turnover of 1 billion rupiah. Therefore it is concluded that the DMNT Sportwear business is worth continuing.